The Effect of Democratic Leadership and Work Motivation on the Loyalty of Kadin Jakarta Barat Management - Ghina Afiah; Nur Asni Gani (Publikasi Indonesia, 2026)
This research aims to examine the effect of democratic leadership and work motivation on the loyalty of administrators of the West Jakarta Chamber of Commerce and Industry (KADIN). Administrator loyalty is a crucial factor for sustaining membership-based non-profit organizations that rely heavily on active participation and long-term commitment. This research employs a quantitative approach with an associative research design. The population consists of all active administrators of KADIN West Jakarta, totaling 50 respondents, with a saturated sampling technique applied. Data were collected through Likert-scale questionnaires and analyzed using multiple linear regression. The findings indicate that democratic leadership has a positive and significant effect on administrator loyalty. Participatory decision-making, two-way communication, and appreciation of opinions strengthen administrators’ sense of belonging and organizational commitment. Furthermore, work motivation also shows a positive influence on loyalty, particularly through intrinsic aspects such as recognition, self-actualization, and opportunities for contribution. Simultaneously, democratic leadership and work motivation significantly contribute to enhancing the loyalty of KADIN West Jakarta administrators. This study provides theoretical contributions to organizational behavior literature and practical insights for non-profit organizations in developing effective leadership styles and motivational strategies to strengthen administrator loyalty.